Adaptive control and the avoidance of cognitive control demands across development. (4th February 2019) - Niebaum, Jesse C.; Chevalier, Nicolas; Guild, Ryan M.; Munakata, Yuko
Abstract: Young adults adaptively coordinate their behavior to avoid demands placed on cognitive control. We investigated how this adaptive coordination develops by having 6–7- and 11–12-year-olds and young adults complete a demand selection task, in which participants could select between two tasks that varied in cognitive control demands via differences in rule switch frequency. Adults and older children exhibited significant preference for selecting the less demanding task, as well as a metacognitive signal guiding adaptive demand avoidance behavior across a variety of behavioral and self-report assessments. In contrast, despite evidence of differential demands on cognitive control, younger children did not coordinate their task selections to avoid higher demand. Together, these findings suggest that sensitivity and adaptive responses to control demands emerge with development and are consistent with gradual development of lateral prefrontal cortex, dorsal anterior cingulate cortex, and their functional connectivity, which support effort avoidance in adults. Highlights: Adults and 11–12-year-olds avoided cognitive control demands but 6–7yo did not, despite all ages exhibiting evidence of demand signals. Adults and 11–12yo but not 6–7yo had subjective awareness of cognitive control demands. Older children may attend to external cues, such as feedback or accurate performance to ascertain demand differences. Adults may develop cognitive demand sensitivity from internal effort signals.